Labrador Inuttut Inverted Number Marking: Ongoing Questions - Smith, Lawrence (Études Inuit Studies, 2019)
There is a fascinating and prima facie perplexing patterning in Inuttut, the Labrador dialect of Inuktitut, wherein the quite regular markers of singular and plural in verbal inflectional markers appear inverted in second person forms. We explore this linguistic problem and show two things: that progress toward a solution is facilitated by incorporating representations of linguistic intent, and also that the consideration of intent, by adding a level of data, opens the phenomenon for deeper understanding by presenting new hypotheses to be explored. Making such features available in grammatical derivations allows the systematic generation of patterns that would otherwise be impossible, thereby obviating gaps in the potential for grammatical explanation and highlighting psychologically plausible mechanisms for diachronic change. It is disadvantageous for any theory of grammatical competence to allow any phenomenon of strong grammatical patterning to remain unaccounted for. By viewing grammatical structures as the result of tool invention by individuals and groups in the linguistic past, the study of the intellectual history of linguistic innovation can potentially uncover particularly clever and insightful processes related to desiderata of cultural adhesion. This approach opens new hypotheses for the evolution of the language from the proto stage.